Given problem;
(-7b + 8c) - (12a + 14) + (5a + 5b) = ?
To this problem, we open the brackets, collect like terms and factor them.
The order of operation, PEMDAS must be strictly adhered to;
P = Parentheses
E = Exponent
M = multiplication
D = Division
A = Addition
S = Subtraction
(-7b + 8c) - (12a + 14) + (5a + 5b);
Open the parentheses;
Note; + x + = +
+ x - = -
- x - = +
- x + = -
So,
= -7b + 8c -12a - 14 + 5a + 5b
Collect like terms;
= 5a -12a + 5b - 7b + 8c -14
= -7a - 2b + 8c -14
The solution is -7a - 2b + 8c -14